Yemeni and regional maritime doctrine in light of the decline of the liberal theory of freedom of navigation in EEZ - Humran, Mohammed Ali (International Journal of Global Operations Research, 2024)
The presence of the USCENTCOM , AFRICOM Â and 34 foreign countries in the vital Yemeni, Arab, and national maritime spheres contributed to a flagrant violation of maritime laws and international political relations. Likewise, the presence and activities of the strategic and tactical military naval units of the aircraft carrier, submarines, and American and British nuclear naval destroyers in the Red Sea. The Gulf of Aden is a breach and violation of international law and agreements regulating freedom of navigation and a blatant assault on Yemeni sovereignty in its vital maritime sphere, as it is located in exclusive Yemeni economic waters, in addition to its nuclear effects in destroying the marine environment and human security. It constitutes a source of danger to food and maritime security, stability, and international peace. The study aims to clarify the influence of Western geopolitical thought and the behavior of American foreign policy in international relations and maritime laws, which is witnessing a major decline and failure in its global policy because it used the policy of American military force to achieve its own political goals and imposed the methodology of Western liberal maritime thought to control and limit the rights of the Yemeni, Arab, and Islamic coastal states. Which contradicts customs, laws, and agreements and affects historical rights and the Yemeni, Arab, and regional maritime domain. The study is expected to confirm the modern Yemeni, Arab, and Islamic hypothesis that the high seas and international maritime waters are within a distance of 200 nautical miles from the baseline and to affirm the right of Yemen and the Arab nation to be protected. The vital area of the United Arab Emirates and the Islamic and regional countries extends from the Atlantic Ocean to the Mediterranean, the Arabian Gulf, the eastern and western Indian Ocean to the Antarctic Ocean, and there is a call for holding maritime conferences in order to develop traditional Western maritime legal theories and concepts that seek to limit the rights of coastal states, establish perceptions, and reach an update to the laws regulating freedom of maritime navigation in accordance with the views of the peoples of the world and in response to global changes in multipolarity.